Differential mobility spectrometry (DMS) reveals the elevation of urinary acetylcarnitine in non‐human primates (NHPs) exposed to radiation. (24th May 2018) - Vera, Nicholas B.; Chen, Zhidan; Pannkuk, Evan; Laiakis, Evagelia C.; Fornace, Albert J.; Erion, Derek M.; Coy, Stephen L.; Pfefferkorn, Jeffrey A.; Vouros, Paul
Abstract: Acetylcarnitine has been identified as one of several urinary biomarkers indicative of radiation exposure in adult rhesus macaque monkeys (non‐human primates, NHPs). Previous work has demonstrated an up‐regulated dose‐response profile in a balanced male/female NHP cohort.1 As a contribution toward the development of metabolomics‐based radiation biodosimetry in human populations and other applications of acetylcarnitine screening, we have developed a quantitative, high‐throughput method for the analysis of acetylcarnitine. We employed the Sciex SelexIon DMS‐MS/MS QTRAP 5500 platform coupled to flow injection analysis (FIA), thereby allowing for fast analysis times of less than 0.5 minutes per injection with no chromatographic separation. Ethyl acetate is used as a DMS modifier to reduce matrix chemical background. We have measured NHP urinary acetylcarnitine from the male cohorts that were exposed to the following radiation levels: control, 2, 4, 6, 7, and 10 Gy. Biological variability, along with calibration accuracy of the FIA‐DMS‐MS/MS method, indicates LOQ of 20 μM, with observed biological levels on the order of 600 μM and control levels near 10 μM. There is an apparent onset of intensified response in the transition from 6 to 10 Gy. The results demonstrate that FIA‐DMS‐MS/MS is a rapid, quantitative technique that can be utilized for the analysis of urinary biomarker levels for radiation biodosimetry.